Leveraging Students’ Achievement and Attitude towards Science through the Integrating of Inquiry-based Learning and Gamification - Sarocha Rompeng; Prasart Nuangchalerm (Journal of Education and Teacher Training Innovation, 2026)
This study examines the inquiry-based learning and gamification effect on the science learning achievement and attitude towards the subject of science. Participants were 45 students enrolled in the second semester, 2025 academic year of secondary school at Roi Et Wittayalai School, Roi Et province, Thailand. The instructional intervention included organized inquiry activities with game features like points, badges, and challenges to student engagement based on constructivist learning theory and motivated learning. Students were placed into experimental research by one-group pretest and posttest design, a standardized science achievement exam was given, and attitude towards science was measured after the intervention. Statistics showed that students had considerably greater post-test scores, higher than the criterion of 70%. The results suggest that inquiry-based learning and gamification can enhance students' understanding and performance in science. Students have a positive attitude towards the subject of science with a high. The negative score was at low level. This study shows that these pedagogical methods might make lower secondary science instruction more engaging and effective for school science.